The Association Between Increment of Interleukin-1 and Interleukin-6 in Women with Polycystic Ovary Syndrome and Body Mass Index - S Mazloomi; z Barartabar; Sh Pilehvari (JRI, 2023)
Background: There is an association between inflammatory factors and polycystic ovary syndrome (PCOS) and most of women with PCOS experience the symptoms of hirsutism. The purpose of this study was to evaluate the role of obesity in PCOS occurrence, which is linked with inflammation and hirsutism. Methods: This study was designed as a case-control research. It was performed on 102 women with PCOS and 102 healthy women as controls who were age-matched. Serum concentrations of testosterone, estradiol (E2), IL-1, IL-6, high-sensitivity c-reactive protein (hs-CRP), and aromatase activity were measured in blood samples. Statistical tests including unpaired t-tests, Mann-Whitney U test, Kruskal-Wallis, Spearman’s correlation, and Chi-square tests were used for data analysis. Statistical significance was set at p<0.05. Results: A significant difference was found between hs-CRP, IL-1, and IL-6 in PCOS patients and healthy individuals (p<0.001). Aromatase activity was markedly lower in PCOS cases. The serum level of IL-1 (p=0.392) and IL-6 (p=0.764) was not different between overweight and normal weight women. In both studied groups (case and control), hirsutism frequency was markedly higher in individuals with BMI ≥25 kg/m2 (p<0.05). Inflammatory factors significantly affected the PCOS group (p<0.05). However, logistic regression showed that hs-CRP increment is more effective on increasing the risk of PCOS (OR: 6.324, p<0.001). Conclusion: In this study, hs-CRP, IL-1, and IL-6 levels increased in all PCOS women. Although the incidence of hirsutism in PCOS is associated with obesity, in PCOS pathogenesis, only IL-1 and IL-6 were independent of BMI.